MENINGKATKAN KETERAMPILAN MEMBACA PEMAHAMAN MENGGUNAKAN MODEL SCRAMBLE PADA PESERTA DIDIK FASE B SEKOLAH DASAR - Nofrianni, Elvima; Prahagia, Yelvia (LPPM Universitas Muhammadiyah Muara Bungo, 2024)
Reading comprehension is very much a polemic in the world of education. The technique for carrying out the reading comprehension process at the elementary school level is still not by the rules; there are still many students in the process of reading comprehension in a text with sound and pointing. This has an impact on students' understanding of reading. This research aims to improve reading comprehension skills through the Scramble model in grade 4 students. The research was conducted at SDN 224/II Sijau, Bungo District, involving 20 students, 15 boys and 5 girls, registered in the 2023 school year/ 2024. This research uses the Kemmis and Mc research design. Taggart, which consists of two cycles. In each cycle, there are two meetings in class, and each cycle consists of four stages: planning, implementation, observation, and reflection. The research results showed that in the first cycle of action, individual absorption capacity was 58.70%, and classical learning completion was 24.56%. There was an increase in cycle II with a classical absorption capacity of 78.40%, while classical learning completeness was 88.27%. Thus, it can be concluded that learning can improve students' ability to read and understand the Scramble model in grade 4 elementary school.